Which Volunteering Settings Do Medical Students Prefer During a Novel Respiratory Virus Pandemic? A Cross-Sectional Study of Multiple Colleges in Central Saudi Arabia During the COVID-19 Pandemic - AlSaif HI; Alessa MM; Alajlan AH; Alrshid AI; Aljarbou AF; Alqahtani AA; Aljumah MI; Alrshid MI; Aleisa AI; Aloufi AM; Alsaad SM (Dove Medical Press, 2022)
Haytham I AlSaif,1 Mohammed M Alessa,2 Ahmed H Alajlan,2 Abdulelah I Alrshid,2 Abdulaziz F Aljarbou,2 Awadh A Alqahtani,2 Mohammad I Aljumah,2 Mansour I Alrshid,3 Aljoharah I Aleisa,4 Abdulrahman M Aloufi,5 Saad M Alsaad1 1Department of Family and Community Medicine, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2College of Medicine, King Saud University, Riyadh, Saudi Arabia; 3College of Medicine, Imam Muhammed Ibn Saud Islamic University, Riyadh, Saudi Arabia; 4College of Medicine, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 5College of Medicine, Almaarefa University, Riyadh, Saudi ArabiaCorrespondence: Haytham I AlSaif, Department of Family and Community Medicine, College of Medicine, King Saud University, P.O. Box 2925, Ext. 34, Riyadh, 11461, Saudi Arabia, Tel +966 114670836, Email hayalsaif@ksu.edu.saPurpose: Novel respiratory virus outbreaks are a recurring public health concern. Volunteering medical students can be a valuable asset during such times. This study investigated the willingness of medical students to volunteer during the coronavirus disease of 2019 (COVID-19) pandemic and the barriers to doing so, considering the possibility of exposure to COVID-19 and mode of contact.Patients and methods: This cross-sectional study was conducted using a self-administered online questionnaire adapted from the literature. The questionnaire comprised four parts: demographic variables, COVID-19-related variables, willingness scale, and barrier scale. The target population was medical students at four different colleges in Riyadh, Saudi Arabia.Results: A total of 802 students participated in the study. A small proportion of students (10.6%) were willing to participate in volunteering activities that could involve contact with patients with COVID-19 as compared to other settings (39.4- 43.4%). More than one-quarter of students (26.8%) had risk factors for severe COVID-19. The main barrier to volunteering was the concern of transmitting the infection to family members (76.8%). Registration to receive the COVID-19 vaccine was positively associated with more willingness to volunteer (β=0.17, p < 0.001), whereas residing in a household with an elderly person was negatively associated (β=− 0.13, p < 0.001). Female sex was positively associated with higher barrier score (β=0.12, p < 0.001).Conclusion: Medical students were more willing to volunteer in activities that did not involve direct contact with patients with COVID-19. A considerable proportion of participants had risk factors for severe illness. Sharing a household with an elderly person or child was associated with lower willingness to volunteer. Organizers of volunteering activities should offer various volunteering options considering the risk of infection; and be mindful of barriers to volunteering, especially risk factors for severe illness and eldercare and childcare responsibilities.Keywords: medical students, volunteerism, health workforce, disaster, pandemic, COVID-19